Individualisation of speed thresholds does not enhance the dose-response determination in football training - Scott, D.; Lovell, R. (Journal of Sports Sciences, 2018)
This study examined the utility of a range of approaches used to develop player-dependent speed zones in time-motion analysis (TMA), in determining the dose-response (internal load) of daily football training. Daily external (10 Hz GPS) and internal load (heart rate metrics, ratings of perceived exertion [RPE], wellness ratings) measures were tracked for 22 International women`s football players during a 21-day training camp. High-speed (HSR) and very high speed running (VHSR) were determined according to arbitrary speed thresholds, as well as using a range of different individualization approaches that included the velocities corresponding to the heart rate deflection point, maximal aerobic speed, YYIR1 performance, and maximal sprint speed (MSS). Within-player correlations between the TMA approaches versus internal load measures quantified the dose-response to training. Correlations between HSR and VHSR vs. RPE were large (r = 0.53-0.67), with the exception of VHSR for the MSS technique (moderate; r = 0.44). HSR was very-largely associated with heart rate indices (r = 0.72-0.78), again with the exception of MSS (large; r = 0.60-0.67). Using a range of different fitness characteristics to individualise speed thresholds did not enhance the dose-response determination to daily fluctuations in external load, and was worsened with MSS per se.